PWE-090 Are Cancers of The Colon Biologically Different Compared to Rectal Cancer?. (17th August 2016) - Patel, A; Peters, F; Shah, J; Ranat, R; Williams, N; Arasaradnam, R
Abstract : Introduction: Emerging evidence suggests that tumour biology of rectal cancers differs from colonic cancer. This study aimed to determine which clinic-pathological factors affect lymph node yield (LNY) and survival in colonic (CC) compared to rectal cancer (RC). Methods: Patients [a1] with stage I-III disease undergoing curative surgery, between 2006 and 2012, were included. Multivariate linear/logistic regression and Kaplan Meier survival analysis with SPSS version 21 were performed. Results: 726 patients (M:F-398: 328, median age-70 years(63–78 yrs) were included (median follow up-58 months-(37–78 months)); 205 patients had RC. Male gender and younger age were associated with RC. A higher LNY was detected with RC compared to CC (median LNY:20 (14–27.5) versus 18 (12–25), p = 0.013). No differences in locoregional recurrence or distant metastases were found (CC 40/521 versus RC 13/205, p = 0.635 and CC 98/521 versus RC 36/205, p = 0.750 respectively). Overall survival (OS) was better in CC compared to RC (mean OS 114 months versus 90 months, p = 0.004); no difference in disease free survival (DFS) was observed. An inadequate LNY (<12 LN) was associated with poor OS in CC compared to RC patients (mean OS-80 months versus 91.5 months, p = 0.027, respectively). On multivariate analysis, T3 stage (p = 0.003), N1 stage (p = 0.016), tumour size (p = 0.018) and mucinous histology (p = 0.018) were associated with an inadequate LNY in CC only and not RC. Conclusion: An inadequate LNY is related to aspects of the primary tumour and is a marker of poor prognosis for CC patients only. No survival differences are observed for RC patients with an inadequate LNY compared to those with >12 lymph nodes questioning the prognostic significance of number of lymph nodes retrieval in RC. Disclosure of Interest: None Declared